Impact of neuroimaging in the pretreatment evaluation of early stage non-small cell lung cancer. Issue 6 (June 2020) - Wasp, Garrett T.; Del Prete, Christopher; Farrell, Jonathan A.D.; Dragnev, Konstantin H.; Russo, Gregory; Atkins, Graham T.; Phillips, Joseph D.; Brooks, Gabriel A.
Abstract: Background: There are limited data and conflicting guideline recommendations regarding the role of neuroimaging in the pretreatment evaluation of non-small cell lung cancer (NSCLC). Methods: We performed a retrospective, pragmatic cohort study of patients with NSCLC diagnosed between January 1 and December 31, 2015. Eligible patients were identified from an institutional tumor registry. We collected all records of pretreatment neuroimaging within 12 weeks of diagnosis, including CT head (CT) and MRI brain (MRI). We abstracted the indication for neuroimaging, presence of central neurologic symptoms and cancer stage (with and without neuroimaging findings) from the tumor registry and the electronic health record. Results: We identified 216 evaluable patients with newly diagnosed NSCLC. 157 of 216 patients (72.7%) underwent neuroimaging as part of initial staging, and 41 (26%) were found to have brain metastases. Of 43 patients with central neurologic symptoms at the time of neuroimaging, 28 (67%) had brain metastasis. In patients without central neurologic symptoms, brain metastases were discovered in 0 of 33 patients with clinical stage I or II, 4 of 36 (11%) with clinical stage III and 9 of 45 (20%) with clinical stage IV disease. Conclusions: In patients with early stage NSCLC (i.e. clinical stage I and II) without central neurologic symptoms, brain metastases are unlikely. The continued use of neuroimaging in the pretreatment evaluation of clinical stage I patients without central neurologic symptoms is not needed. Abstract : Health Sciences; Oncology; Medical Imaging; Radiology; Diagnostics; Non-small cell lung cancer; MRI brain; pretreatment evaluation; CT head; staging; outcomes.